Integration of Prismatic Science and Development of Arabic Education Master Curriculum - Erlina, Erlina; Khalid, Idham; Muslim, Ahmad Bukhari (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This article described the curriculum development of the Arabic Education (AE) Master’s program in accordance with the university's vision through research and development of the Borg and Gall’s model with a qualitative approach, data collection through documentation, literature review, and questionnaires for expert validation. The performance of education personnel’s who are less adaptive to the advancement of science and technology is one of the problems faced by the world of education. The cause of this problem is that the education curriculum for education personnel’s is not relevant to the users’ changing needs. Hence, the higher education curriculum needs to be developed according to the demands of social change and the progress of today's science to realize a relevant curriculum. Data analysis was done through the stages of data reduction, data display, and conclusion. The results of the study resulted in a curriculum model which refers to the Indonesian National Qualifications Framework (IQF) based on prismatic science integration. This curriculum model is expected to produce master's graduates who are able to act as Arabic language teachers at the undergraduate level who are professional, innovative, and creative in developing Arabic language education through research and scientific publications and have Ulul Albab, Ulil Abshor, and Ulin Nuha characters that radiate in thought and activity.